OPTIMALISASI E-JURNAL SEBAGAI PRODUK ULANG INFORMASI DI UNIVERSITAS BAITURRAHMAH - Wahyuli, Mira (Jurnal Informasi, Perpustakaan, dan Kearsipan (JIPKA), 2025)
This study aims to analyze the optimization of e-journals as repackaged information products to enhance the utilization of digital resources by students and lecturers at Universitas Baiturrahmah. The background of this research is the low level of e-journal usage despite the availability of access through various academic platforms. This research employs a qualitative approach with descriptive methods. Data were collected through direct observation and semi-structured interviews with librarians. The results reveal that e-journal utilization remains low, with only 10"“20% of students actively accessing them, mainly those in their final year. Many students lack awareness of e-journal usage and struggle with access and search mechanisms. To address this, the library has implemented various information repackaging strategies such as infographics, video tutorials, and social media content. Librarians play a crucial role as access facilitators, information literacy educators, and content curators. The study concludes that information repackaging is effective in bridging the gap in access and understanding of e-journals. Sustainable efforts are needed through continuous digital literacy training, academic collaboration, and innovative information services to ensure that e-journals become an integral part of the learning and research process in higher education.